Migrazioni in Italia: oltre la sfida Per un approccio interdisciplinare allo studio delle migrazioni - BULLI, GIORGIA; Tonini, Alberto (Studi e saggi, 2021)
'Going beyond the challenge' means looking at the phenomenon of migration in its complexity, through a multi and interdisciplinary approach. The chapters that make up the first part offer an over-view of the phenomenon, with a reflection on the numbers of migrations in Italy followed by an in-depth examination of its international dimension. The second part focuses on the Italian case, and on the Italian foreign policy towards some African countries. The third part of the book adopts a sociological perspective, including the reconfiguration of the 'border' in Italian legislation and the analysis of the reception model promoted in Tuscany. The fourth part analyses public communication, from hate speech to stereotypes, up to the politicization of the migration issue in some European countries.